"Consumers don't see tigers dying in palm oil plantations": a cross-cultural comparative study of UK, Malaysian and Singaporean consumer views of palm oil. Issue 2 (3rd July 2019) - Reardon, Katharine; Padfield, Rory; Salim, Hengky K.
ABSTRACT: In the past decade, palm oil has become the most produced and consumed vegetable oil globally. In view of the growing global demand for palm oil, promoting consumption of the most "sustainable" form of palm oil is necessary to mitigate the known environmental and social impacts of unsustainable production. In this study, we compare consumer awareness, knowledge, and perceptions of palm oil and its sustainability amongst consumers from three countries: Malaysia, Singapore and the UK. Employing a combination of an online survey, interviews and focus groups and building on consumer behavior theories, we found a number of key differences and similarities between the three nationalities. Malaysians were more aware of palm oil and held more positive views compared to the other two nationalities, while all were relatively unfamiliar with the concept of "sustainable palm oil". Only a small proportion of respondents from each country ruled out purchasing sustainably certified palm oil products. However, price was a determining factor and most respondents from the three countries were unwilling to pay more for "green" products. Considering the disconnect felt by consumers towards the realities of palm oil production, we argue for improved consumer-facing information on the socio, economic and environmental impacts of their consumption patterns. Finally, the study highlights the importance of place in shaping consumer views of palm oil and thus a need to better understand how positive information campaigns about the benefits of sustainable production can sit alongside localized information flows of palm oil.